Internalisasi Pendidikan Kristiani dalam Keluarga - Stevie Cornelia Kimbal; Johanna Setlight; Deflita R.N. Lumi (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to understand the meaning of internalizing Christian education and its practice in the family. The internalization of Christian education is the process of instilling Christian values. Instilling Christian values ​​first and foremost is in the family, a child's character is formed starting from the family. Christian education leaders such as Martin Luther, Horace Bushnell and Nieke Atmadja Hadinoto said that the family has a very important role in the formation of children's faith, and that parents are the most responsible for educating their children, because parents have the closest relationship with their children. The focus of this research is the family in the GMIM Canaan Ranotana Weru Congregation. The method used is descriptive qualitative research methodology. In this study, it was concluded that the lack of methods and techniques for carrying out Christian education in the family was caused by an inadequate understanding of how to teach and guide children, as well as a lack of willingness to spend time with family and the willingness to learn together in developing children's faith. children in the family at home are less cared for and this is ignored by parents.